Mandat Ilahi tentang Menggembalakan Domba - Indriati Tjipto Purnomo (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2022)
Shepherd is one of the four kinds of offices that are given responsibility by God and placed in the church and function for building the body of Christ. The shepherd is the leader who brings the congregation to maturity in Christ, Ephesians 4:11. God calls and places someone to be a shepherd to carry out the Divine mandate, which is to shepherd the sheep. The linguists in this study use a qualitative method, namely a theological review presented using literature or literature studies.